ISSUES OF IMPROVING THE INCOME GENERATION STRATEGY IN COMMERCIAL BANKS - Kunduzova Kumrixon Ibragimovna (Modern American Journals, 2025)
This article discusses the challenges of optimizing the revenue-generating strategy of commercial banks. It analyzes the primary sources of income for banks, including interest, commission, and transaction income from securities, factoring, and trust management, as well as other activities. Particular attention is given to credit policies as a crucial element in ensuring the financial stability and profitability of banks. Additionally, the paper examines issues related to centralization and decentralization of management, inadequate analysis of borrower financial condition, and weak monitoring of credit processes. Based on a study of theoretical and regulatory resources, measures are suggested to optimize income and expense accounting, which could enhance the competitiveness of banks and their market position.
Keywords: Commercial banks, income, credit policy, factoring, trust management, interest margin, financial services, development strategy.